Fall-related traumatic brain injury in children ages 0–4 years. (September 2019) - Haarbauer-Krupa, Juliet; Haileyesus, Tadesse; Gilchrist, Julie; Mack, Karin A.; Law, Caitlin S.; Joseph, Andrew
Abstract: Introduction : Falls are the leading cause of traumatic brain injury (TBI) for children in the 0–4 year age group. There is limited literature pertaining to fall-related TBIs in children age 4 and under and the circumstances surrounding these TBIs. This study provides a national estimate and describes actions and products associated with fall-related TBI in this age group. Method : Data analyzed were from the 2001–2013 National Electronic Injury Surveillance System–All Injury Program (NEISS–AIP), a nationally representative sample of emergency departments (ED). Case narratives were coded for actions associated with the fall, and product codes were abstracted to determine fall location and product type. All estimates were weighted. Results : An estimated 139, 001 children younger than 5 years were treated annually in EDs for nonfatal, unintentional fall-related TBI injuries (total = 1, 807, 019 during 2001–2013). Overall, child actions (e.g., running) accounted for the greatest proportion of injuries and actions by others (e.g., carrying) was highest for children younger than 1 year. The majority of falls occurred in the home, and involved surfaces, fixtures, furniture, and baby products. Conclusions : Fall-related TBI in young children represents a significant public health burden. The majority of children seen for TBI assessment in EDs were released to home. Prevention efforts that target parent supervision practices and the home environment are indicated. Practical applications : Professionals in contact with parents of young children can remind them to establish a safe home and be attentive to the environment when carrying young children to prevent falls. Highlights: Falls are the leading cause of traumatic brain injury (TBI) in children ages 0–4 years. This study provides a national estimate and describes actions and products associated fall-related TBI in young children. Prevention efforts in this age group include consideration of both child development and parental supervision practices. Professionals can remind caregivers to attentive to a child's environment to prevent falls that can result in a TBI.